Comparative Literature: Exploring Folktales “Ular N’daung Dan Si Bungsu” And “The Legend of White Snake” - Dyah Ratna Mufidah; Arju Susanto; Kurnia Rachmawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Folktales are one of the widespread literary works in the community. Folktales in one region may differ in themes, storylines, and aspects from the other. Examples of such differences can be seen in the Indonesian folktale "Ular N’Daung dan Si Bungsu" and the Chinese folktale "The Legend of the White Snake." This study aims to describe the division of episodes and socio-cultural factors contained in the two stories. This research uses a descriptive-qualitative approach. The data collection technique used in this research is library research. The research data were analyzed using the structuralism theory and described qualitatively. The results showed that these two folktales both have a similar plot that consists of the initial meeting, conflict, and resolution. The difference lies in the number of episodes and storylines, considering that the length of the folktales is also different.